Properties of tennis racket made by differential carbon fibre - Chiang, J.-Y.; Chiang, C.-C.; Chen, T.-Y.; Yang, J.-H. (ISB Congress, 2005)
Rackets general are made of new material high strength carbon or graphite composite. Carbon fibre used most often and it is usually combined with high strength carbon fibre. The purpose of this study was to investigate the vibration of various tennis rackets, which were composed by the mixture of high strength carbon fibre and general carbon fibre. The authors concluded that the forearm can be easily fatigue in such a high-impact power tennis players. This high-frequency vibration caused much greater stress on the joint of the hand and arm. Then, indirectly, this phenomenon might affect the athlete's performance.